Reduced Oral Bioavailability and Altered Pharmacokinetics of Saquinavir by Co-administration with Biochanin A in Rats - Li, J.; Liu, Y.; Yu, X.; Zhang, J.; Gu, J.; Zhao, L. (Drug Research, 2016)
The study was aim to assess the impact of biochanin A on the oral bioavailability and pharmacokinetics (PK) of saquinavir (SQV), a substrate of P-glycoprotein (P-gp), in rats. 10 male rats were randomized into 2 groups of equal size, and administered orally 30 mg/kg SQV with or without 20 mg/kg biochanin A. The PK of SQV was assessed using non-compartmental analysis. Results revealed that the area under the plasma concentration-time curve of SQV from time zero to time infinity (AUC0-∞) was reduced by 51.39% by biochanin A (P=0.038); while the apparent systemic clearance (CL/F) was increased by 87.62% (P=0.028). Double peak phenomenon was observed in the plasma SQV profiles. Biochanin A increased the first peak, yet decreased the second peak of plasma SQV levels. Our study demonstrates that biochanin A can significantly reduce SQV oral bioavailability and alter SQV PK profiles in rats. Findings in this study suggest a precaution in the clinic when SQV is administered with dietary/herbal supplements that contain biochanin A.
Keywords: absorption; antiviral drugs; drug-drug interaction; P-glycoprotein